Beyond Talent Management: The Critical Role of Flexible Working Arrangements in Enhancing Public Sector Job Satisfaction - Azis, Saepul; Prasetyaningtyas, Sekar Wulan (Dinasti Publisher, 2026)
This study assesses the impact of talent management and flexible working arrangements on job satisfaction and employee performance, especially in the public sector post-merger period. The data is collected by employee of Indonesia’s research and innovation agency which has merged with several research and development institutions. The author also explains more about the effect of talent management and flexible working arrangements on employee performance, which is influenced by job satisfaction. This study uses talent management and flexible working arrangements on job satisfaction and employee performance in the public sector institutions of research and innovation in Jakarta area by using variables that affect employee performance. Questionnaire were distributed online to 182 employee respondent who worked at research and innovation agency in the Jakarta area. The data were then analyzed using PLS-SEM through SmartPLS 4 software. The results of this study indicate a non significant effect of talent management on job satisfaction and employee performance. And conversely, the effect of flexible working arrangements on job satisfaction is positive significant. Employees value the ability to control their time and environment of flexible working arrangements, which directly translates to higher satisfaction.